2021
DOI: 10.1186/s12868-021-00655-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of rat ADSCs encapsulation in fibrin matrix and combination delivery of BDNF and Gold nanoparticles on peripheral nerve regeneration

Abstract: Background Fibrin as an extracellular matrix feature like biocompatibility, creates a favorable environment for proliferation and migration of cells and it can act as a reservoir for storage and release of growth factors in tissue engineering. Methods In this study, the inner surface of electrospun poly (lactic-co-glycolic acid) (PLGA) nanofibrous conduit was biofunctionalized with laminin containing brain derived neurotrophic factor (BDNF) and gol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 44 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…We successfully isolated primary ADSCs, identified the surface antigens using flow cytometry, and confirmed their adipogenic and osteogenic abilities through direction-induced differentiation. ADSCs promote the repair of PNIs; however, it has been reported that a paracrine mechanism is involved in MSC-mediated tissue repair, whereas direct differentiation of stem cells is weak [ 24 , 25 ]. Considering the limitations of stem cell applications and the fact that the paracrine function of stem cells can be mediated by exosomes, the use of exosomes to replace stem cells for direct treatment has become a feasible alternative method.…”
Section: Discussionmentioning
confidence: 99%
“…We successfully isolated primary ADSCs, identified the surface antigens using flow cytometry, and confirmed their adipogenic and osteogenic abilities through direction-induced differentiation. ADSCs promote the repair of PNIs; however, it has been reported that a paracrine mechanism is involved in MSC-mediated tissue repair, whereas direct differentiation of stem cells is weak [ 24 , 25 ]. Considering the limitations of stem cell applications and the fact that the paracrine function of stem cells can be mediated by exosomes, the use of exosomes to replace stem cells for direct treatment has become a feasible alternative method.…”
Section: Discussionmentioning
confidence: 99%
“…50 In addition, the synergy of AuNPs with silk not only improves nerve myelination and complex movements in mice (such as stretching and jumping), but also provides the best electrophysiological function in regenerated sciatic nerves. In this regard, Afjeh-Dana et al 51 confirmed that the presence of AuNPs in the silk fibroin/ AuNPs nanocomposite increases the adhesion of stem cells, high proliferation and overexpression of Nestin and enolase proteins, along with improving the poor electrical conductivity 52 Also, compared to the results of Qian et al, 48 this research demonstrated that the conduit performance is similar to autografts in nerve regeneration, which can be one of the desirable solutions to reduce the challenge of insufficient autograft resources. 52 In confirmation of the above findings, Razavi et al 52 used markers S100 (for Schwann cells) and NF200 (for axon fibers) in the immunohistochemistry method, showing that the average intensity of S100 and NF200 in the group containing AuNPs is similar to autograft samples from other groups.…”
Section: Effect Of Aunp Physicochemical Structure On Pnmentioning
confidence: 96%
“…In this regard, Afjeh-Dana et al 51 confirmed that the presence of AuNPs in the silk fibroin/ AuNPs nanocomposite increases the adhesion of stem cells, high proliferation and overexpression of Nestin and enolase proteins, along with improving the poor electrical conductivity 52 Also, compared to the results of Qian et al, 48 this research demonstrated that the conduit performance is similar to autografts in nerve regeneration, which can be one of the desirable solutions to reduce the challenge of insufficient autograft resources. 52 In confirmation of the above findings, Razavi et al 52 used markers S100 (for Schwann cells) and NF200 (for axon fibers) in the immunohistochemistry method, showing that the average intensity of S100 and NF200 in the group containing AuNPs is similar to autograft samples from other groups. Also, the increase in the average diameter of atrophied gastrocnemius muscle fibers caused by sciatic nerve injury in the designed conduit, similar to autograft, compared to other groups indicates the positive performance of AuNPs.…”
Section: Effect Of Aunp Physicochemical Structure On Pnmentioning
confidence: 96%
“…Other natural materials, including native fibrin ( Du et al, 2017 ; Wang et al, 2018 ; Razavi et al, 2021 ), collagen ( Saeki et al, 2018 ; Yao et al, 2018 ; He et al, 2021 ; Wang et al, 2021 ; Zheng et al, 2021 ), keratin ( Apel et al, 2008 ; Lin et al, 2012 ; Pace et al, 2014 ), alginate ( Lin et al, 2017 ; Rahmati et al, 2021 ; Abdelbasset et al, 2022 ), chitin ( Bak et al, 2017 ; Lu C. F. et al, 2021 ; Yang et al, 2022b ), chitosan ( Li et al, 2018 ; Vishnoi et al, 2019 ), and silk fibroin ( Carvalho et al, 2021 ; Kim et al, 2021 ; Zhao et al, 2020), as well as extracellular matrix (ECM) ( Li T. et al, 2021 ; Kong et al, 2021 ; Kong et al, 2022 ), have shown great potential in treating long gap nerve defects. For instance, Wang et al prepared a nerve catheter using chitosan/chitin to achieve excellent angiogenesis in nerve regeneration process for successfully repairing the 10 mm sciatic nerve defect in rats ( Wang et al, 2016 ).…”
Section: Research Progress Of Peripheral Nerve Graftsmentioning
confidence: 99%